Study of prescribing pattern of antihypertensive drugs in diabetic patients in a tertiary care centre, Vizianagaram, India - Elenchezhiyan, Vanathi; Moorthy, Sachidananda; K., Sagar M.; Mattam, Bheemesh Naidu; Sayana, Suresh Babu (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes mellitus (DM) and Hypertension (HTN) are the two major chronic disorders frequently coexisting, with increased incidence with age. HTN is about twice as common in patients with DM. Prescribing pattern are powerful tools to ascertain the role of drugs in society. There are many variations in prescribing patterns of antihypertensive drugs in patients with HTN and DM. Since these patients requires lifelong treatment it has enormously increased the burden of patients particularly in developing countries like India. Physician needs to be more concerned while choosing drugs for the patients with HTN and DM. In a tertiary care hospital, there is a real need for drug utilization study to determine the appropriate, more safe and effective patterns of drug therapy among diabetic hypertensive patients. Methods: A Cross sectional observational study was conducted in Maharajah’s Institute of Medical Sciences from December 2016 to May 2018. A total of 360 prescriptions of the patients with hypertension and coexisting diabetes were analyzed. The prescriptions prescribed to these patients were collected, assessed and the following parameters were noted. The treatment pattern of different group of drugs for HTN with co-existing DM was evaluated. The intended work was divided into three steps: Step 1: To collect the prescriptions of hypertensive patients with DM. Step 2: To separate the prescriptions prescribing anti hypertensive Drugs. Step 3: To statistically analyze the prescriptions. Relevant information was recorded in a structured proforma & data was evaluated. Results: In this study it was found that 36% of the patients were in the age group of 51-60 years with female preponderance among diabetic hypertensive patients. 77% of patients were treated with single antihypertensive drug and 23% of patients were treated with antihypertensive drug combinations. In monotherapy, telmisartan was most commonly prescribed. In combination therapy, amlodipine and telmisartan followed by amlodipine and atenolol were used. Conclusions: In this study monotherapy was preferred compared to combination therapy and adherence to the JNC 7 guidelines was good except in case of usage of diuretics.